EFFECT OF CONSUMING TAMARIND AND TURMERIC DRINK ON THE LENGTH OF PERINEAL WOUND HEALING IN POSTPARTUM MOTHERS - Dewi Susanti; Onny Setiani; Umaroh Umaroh; Kun Aristiati; Imam Djamaluddin Mashoedi; Mardiyono Mardiyono (Belitung Nursing Journal, 2017)
Background: The incidence of perineal tear is still high in Indonesia. It is therefore the intervention to accelerate wound healing is needed. The use of turmeric and tamarind is considered as the alternative treatment for wound healing. However, little is known about the effect of the combination of turmeric and tamarind. Objective: To determine the effect of consuming turmeric and tamarind on the duration of perineal wound healing. Methods: The study was a quasi-experimental study with one group post-test only design conducted in the working area of the Community Health Center of Ngesrep and Srondol, Semarang City, Central Java, Indonesia in December 2016 until January 2017. There were 28 respondents recruited using consecutive sampling, with 14 randomly assigned in each group. The REEDA scoring system was used to measure the wound healing. Data were analyzed using Independent t-test. Results: The results revealed that the average duration of wound healing in the intervention group was 6.25 days, while in the control group was 8.57 days with p-value 0.000 (<0.05), which indicated that there was statistically significant effect of tamarind turmeric drink of the duration of perineal wound healing in postpartum mothers. Conclusion: There was a significant effect of turmeric tamarinds drink on the duration of perineal wound healing in postpartum mothers. It is therefore suggested to the health providers, especially midwives, to apply this intervention the accelerate healing of perineal wound in postpartum mothers.